2020
DOI: 10.3389/fnagi.2020.535770
|View full text |Cite
|
Sign up to set email alerts
|

Functional Connectivity of Successful Picture-Naming: Age-Specific Organization and the Effect of Engaging in Stimulating Activities

Abstract: Aging is a lifelong process that starts at birth. Throughout the course of their life, individuals are exposed to various levels of stimulating activities. A higher level of engagement in such activities is suspected to protect against the normal course of cognitive aging or the cognitive manifestations of age-related brain diseases. However, the exact mechanism underlying such protective action remains unclear. The concept of the neurocognitive reserve was introduced to refer to the hypothesis that engagement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 115 publications
(149 reference statements)
1
2
0
Order By: Relevance
“…These findings are consistent with previous evidence indicating that higher rates of vocabulary learning correlate with beta power modulations 81 . Additionally, better performance in picture‐naming negatively correlates with rsFC in the DMN, 82,83 as indexed here by delta dynamics. Furthermore, in the bilingual domain, beta 20,21 and delta 84 connectivity have been shown to correlate with L2 learning proficiency.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with previous evidence indicating that higher rates of vocabulary learning correlate with beta power modulations 81 . Additionally, better performance in picture‐naming negatively correlates with rsFC in the DMN, 82,83 as indexed here by delta dynamics. Furthermore, in the bilingual domain, beta 20,21 and delta 84 connectivity have been shown to correlate with L2 learning proficiency.…”
Section: Discussionsupporting
confidence: 92%
“…These stimuli have been used successfully in the past to create semantic memory networks across several studies, labs, and languages (Benedek et al, 2017;He et al, 2021;Ovando-Tellez et al, 2022). Prior work in the aging literature has shown that during picture naming word retrieval, older adults have lower accuracy for low-frequency items compared to younger adults (Burke et al, 1991;Ferre et al, 2020;Gertel et al, 2020), which suggests that even larger agerelated differences may be found with less frequent words. Future studies should expand the breadth of cue words to include lower frequency items that may lie along the periphery of the semantic network and may reveal greater age-related differences.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…From now on, we shall refer to components as “networks” and we will identify components by referring to their label (e.g., DMN); component descriptions are listed in Supplementary Table 1 . For the spatial map, we examined how the PSA-related network structure differed between the two groups using a voxel-wise F-test (group main effect), as in previous studies ( 36 ).…”
Section: Methodsmentioning
confidence: 99%